2021
DOI: 10.1007/s12594-021-1822-z
|View full text |Cite
|
Sign up to set email alerts
|

Source Parameters of Shallow Microtremors Induced by Seasonal Groundwater Recharge in Hyderabad, Southern Peninsular India

Abstract: Source parameters were estimated using multiple empirical Green’s functions (meGf) method for 2 clusters of shallow depth and small-magnitude earthquakes induced by the infiltration due to gravity into the groundwater zone after heavy monsoons during October 1998 and October 2017, in Hyderabad, South India. First, four decades of earthquake catalogue data recorded by HYB seismic station at CSIR-National Geophysical Research Institute (NGRI) was used to characterize the spatiotemporal variation in seismicity. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The 2011 Sikkim earthquake had about five aftershocks of magnitude (mb) ≥ 4.5 between 2011 and 2014 for the same region. Parvin et al (2021) analyzed two swarm activities in the Hyderabad region and found small absolute stress drop values (< 1 MPa) and a positive correlation between the static stress drop and the magnitude of the earthquake with seismic moment varying between -0.09 < M L < 1.52. They observed a clear correlation of earthquakes associated with the fractures and faults in the vicinity of water bodies which are more sensitive to variations in hydrostatic pressures caused by vertical flow recharge from rainfall and deeper pore-fluid pressure diffusion.…”
Section: Study Of Earthquake Swarmsmentioning
confidence: 99%
“…The 2011 Sikkim earthquake had about five aftershocks of magnitude (mb) ≥ 4.5 between 2011 and 2014 for the same region. Parvin et al (2021) analyzed two swarm activities in the Hyderabad region and found small absolute stress drop values (< 1 MPa) and a positive correlation between the static stress drop and the magnitude of the earthquake with seismic moment varying between -0.09 < M L < 1.52. They observed a clear correlation of earthquakes associated with the fractures and faults in the vicinity of water bodies which are more sensitive to variations in hydrostatic pressures caused by vertical flow recharge from rainfall and deeper pore-fluid pressure diffusion.…”
Section: Study Of Earthquake Swarmsmentioning
confidence: 99%